2023
DOI: 10.3389/fpubh.2023.1043696
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of self-reported adverse events related to COVID-19 vaccines in Saudi Arabia: A nationwide study

Abstract: BackgroundVaccination against coronavirus disease 2019 (COVID-19) is the most effective way to end the pandemic. Any development of adverse events (AEs) from various vaccines should be reported. We therefore aimed to explore major and minor AEs among vaccinated individuals in Saudi Arabia.MethodsThis is a nationwide report based on the Saudi Arabian Ministry of Health (MOH) registry. It included those who received COVID-19 vaccines from 17th December 2020 to 31st December 2021. The study included spontaneous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Research by Abu-Hammad et al(2021) in Jordan also got results that the most common reaction was breathing difficulty which was experienced by 19 people (4,6%). [46] Similar results were also obtained in a research byAlkhalifah et al (2023) in Saudi Arabia where from a total sample of 28.031 people, there were 1.736 people (6,19%…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Research by Abu-Hammad et al(2021) in Jordan also got results that the most common reaction was breathing difficulty which was experienced by 19 people (4,6%). [46] Similar results were also obtained in a research byAlkhalifah et al (2023) in Saudi Arabia where from a total sample of 28.031 people, there were 1.736 people (6,19%…”
supporting
confidence: 77%
“…who experienced breathing difficulty. [47] Breathing difficulty can occur as an immune response. Another source states that breathing difficulty could be related to immunization stress-related responses (ISRRs), which is one of the AEFIs that is not caused by the components contained in the vaccine, but rather by the vaccination process itself.…”
Section: Aefi Of Covid-19 Vaccine In Balimentioning
confidence: 99%
“…Guillain–Barre syndrome (GBS) is an acute immune-mediated polyradiculoneuropathy that affects myelinated nerves. GBS is a severe complication after COVID-19 vaccination and a common cause of intensive care unit admission [ 2 , 52 ]. Most GBS cases were reported after the first dose of the vaccine [ 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from 2011 highlighted that 7-45% of the U.S. population experiences persistent fatigue [34]. A cross-sectional study involving 2063 individuals showed that over 50% of patients were troubled by fatigue in Saudi Arabia [35]. Importantly, women appear to be more susceptible to fatigue than men, with a pooled odds ratio [33].…”
Section: Epidemiology Of Fatiguementioning
confidence: 99%